2022
DOI: 10.1039/d2cc04015h
|View full text |Cite
|
Sign up to set email alerts
|

Markovnikov-selective double hydrosilylation of challenging terminal aryl alkynes under cobalt and iron catalysis

Abstract: Bench-stable complexes with a tridentate ligand serve as precatalysts in the synthesis of geminal bis(silanes) from terminal aryl alkynes regarded as challenging substrates in this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The 11 B NMR spectrum acquired for structure 2 (Scheme 10c) indicates the presence of several diverse boron nuclei (see the ESI †), probably originating from BEt 3 adducts with the anionic form of the complex, which is in agreement with the literature reports by the Pawluć group. 59 In the case of the non-anionic form, its lower catalytic activity is probably compensated by the β-silicon effect, stabilizing the alkyl complex and remarkably accelerating the reaction rate. [60][61][62] Based on this and our previous studies on pincer cobalt complexes, as well as literature reports, [44][45][46]57,[63][64][65][66][67] we postulate that in the reaction mixture, as a result of activation with pinacolborane or sodium triethylboron hydride, the two Scheme 9 Experiments verifying the potential formation of borane as a hidden reaction catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 11 B NMR spectrum acquired for structure 2 (Scheme 10c) indicates the presence of several diverse boron nuclei (see the ESI †), probably originating from BEt 3 adducts with the anionic form of the complex, which is in agreement with the literature reports by the Pawluć group. 59 In the case of the non-anionic form, its lower catalytic activity is probably compensated by the β-silicon effect, stabilizing the alkyl complex and remarkably accelerating the reaction rate. [60][61][62] Based on this and our previous studies on pincer cobalt complexes, as well as literature reports, [44][45][46]57,[63][64][65][66][67] we postulate that in the reaction mixture, as a result of activation with pinacolborane or sodium triethylboron hydride, the two Scheme 9 Experiments verifying the potential formation of borane as a hidden reaction catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The 11 B NMR spectrum acquired for structure 2 (Scheme 10c) indicates the presence of several diverse boron nuclei (see the ESI†), probably originating from BEt 3 adducts with the anionic form of the complex, which is in agreement with the literature reports by the Pawluć group. 59 In the case of the non-anionic form, its lower catalytic activity is probably compensated by the β-silicon effect, stabilizing the alkyl complex and remarkably accelerating the reaction rate. 60–62…”
Section: Resultsmentioning
confidence: 99%
“…The use of rare-earth La ( Chen et al, 2020 ) or borane catalysts ( Wang et al, 2021 ) provided alternative strategies that render such a limitation mitigated to certain extents, furnishing geminal disilylalkanes from aryl alkynes via initial Markovnikov or anti-Markovnikov hydrosilylation, respectively. In 2022, Banach et al (2022) demonstrated that Co catalysts are also effective for the dihydrosilylation of alkynes bearing an aryl substituent ( 8 ), albeit requiring elevated reaction temperatures. The initial screening involved the use of Fe catalysts and Fe/Co dual conditions, but Co4 with an N , N , N -tridentate hydrazone ligand was shown to be most efficient for the reaction employing Si1 , NaHBEt 3 , and THF solvent ( Scheme 5 ).…”
Section: Co-catalyzed Dihydrosilylation Of Alkynesmentioning
confidence: 99%
“…Thus, proteins that contain regions rich in histidine and cysteine residues are an interesting case of ligands due to a high affinity to bind Zn(II), Ni(II) and Fe(II) [ 6 , 7 , 8 , 9 ] and are chosen both by nature and by science as good metal chelators. Knowledge about the coordination mode, structure and function of specific binding sites in biomimetic artificial ligands with SH/NH groups and their metal complexes biomolecules provides us knowledge that can be transferred to a new generation of materials and applications, such as catalysis [ 10 ], bioassays [ 11 ] or general peptide-governed metal sorption [ 12 , 13 ]. It is important to note that often, seemingly very similar coordination motifs (as also in the case of this work) do not necessarily lead to the same coordination and functional outcomes, which are important factors to consider in the design of novel biomimetics, catalysts and materials [ 14 ].…”
Section: Introductionmentioning
confidence: 99%